Description of the dermal denticles on pre-pelvic claspers of the Cockfish, Callorhinchus callorynchus (Holocephali: Callorhinchidae), from Coquimbo, Chile - López-Jofré, Álvaro; Hernández, Sebastián; Flores, Héctor (Revista de Biología Marina y Oceanografía, 2023)
Chimaeras or Ghost sharks (Subclass Holocepahli) have sexual structures called pre-pelvic claspers, and these structures are covered by dermal denticles. In this study, dermal denticles present in pre-pelvic claspers of the Cockfish, Callorhinchus callorynchus, were described in order to compare them with those of other known species of this subclass. Pre-pelvic claspers of 22 specimens were removed for further examination. Dermal denticles on the flat surface of pre-pelvic claspers were different when examining their size, shape, and number of cusps. Dermal denticles were classified as type A (three cusps), B (four cusps), C (five cusps), D (six cusps) and E (eight cusps). Dermal denticles with fewer cusps were located near the center, whereas those with more cusps were located towards the periphery. All types of dermal denticles were found in the largest individuals (> 40 cm length). Possible functions of the dermal denticles and the pre-pelvic clasper in the reproductive activity of this species are suggested.